Ruang Lingkup Administrasi Pendidikan: Tantangan dan Solusi dalam Meningkatkan Efisiensi Sekolah - Fathimah, Meti; Ghafur, Octa Abdul; Winarno, Andhika Sarfatra (Lembaga Yasin AlSys, 2024)
Educational administration plays a pivotal role in ensuring the smooth operation and efficiency of educational institutions at all levels. This paper discusses the scope of educational administration, focusing on key functions such as planning, organizing, implementing, and monitoring. In addition, it examines the common challenges faced in the practical implementation of educational administration, such as limited human resources, inadequate funding, and minimal external support. By offering practical solutions to these challenges, this study aims to contribute to the development of more efficient administrative practices, thereby enhancing the quality of education and achieving broader educational goals.